2013
DOI: 10.2478/pjct-2013-0076
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of spent brewer’s yeast for supplementation of distillery corn mashes

Abstract: The aim of the study was to use spent brewer's yeast biomass (SBY) as a nutrient adjunct of distillery type corn mashes to improve the process of ethanol fermentation by yeast Saccharomyces cerevisiae. There were prepared corn mashes with raw material loading at 20% ww. with SBY addition at solids loadings of 0 (control); 0.1; 0.5; 0.7; 1.0; 3.0 and 5.0% ww. The obtained mashes were inoculated with yeast and subjected to batch fermentation for 72 h. It was observed that supplementation of corn mashes with SBY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Moreover, brewery spent yeast can be applied as nutrients during ethanol or lactic acid fermentation [238,239]. Pietrzak and Kawa-Rygielska [240] showed that the 5% addition of brewery spent yeast might increase the rate of sugar consumption and ethanol production resulting in even 11% enhancement of ethanol yield. Such an effect was ascribed to the high nitrogen content of the medium.…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…Moreover, brewery spent yeast can be applied as nutrients during ethanol or lactic acid fermentation [238,239]. Pietrzak and Kawa-Rygielska [240] showed that the 5% addition of brewery spent yeast might increase the rate of sugar consumption and ethanol production resulting in even 11% enhancement of ethanol yield. Such an effect was ascribed to the high nitrogen content of the medium.…”
Section: Current Applications and Potential In Polymer Technologymentioning
confidence: 99%
“…Microbial protein may also be a coproduct to be recovered after industrial processes, such spent yeast (Patent No. US 9,963,671 B2, 2018) or algae (Chandra, Iqbal, Vishal, Lee, & Nagra, 2019;Laurens et al, 2017) from biorefineries and brewery industries (Pietrzak & Kawa-Rygielska, 2013;Vieira, Cunha, & Ferreira, 2018). Additionally, molecular biology techniques have been employed to improve or add value to the processes, such as improvement of metabolic routes for the use of agro-industrial wastes in simultaneous production of SCP and lipase by Yarrowia lipolytica (Yan et al, 2018).…”
Section: Microbial Proteinmentioning
confidence: 99%